1964
DOI: 10.1099/00221287-35-1-81
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic and Genetic Control of Polyphosphate Accumulation in Aerobacter aerogenes

Abstract: SUMMARYAddition of orthophosphate to Aerobacter aerogezzes strain A 3( 0) organisms previously subjected to phosphate starvation induced accumulation of inorganic polyphosphate within the organisms. With resumption of growth the polyphosphate was degraded and served as a source of nucleic acid phosphorus. During phosphate starvation the specific activity of polyphosphate kinase and inorganic polyphosphatase increased five-to tenfold while the amount of alkaline phosphatase increased 50 times. The results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1
1

Year Published

1982
1982
1990
1990

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 13 publications
1
32
1
1
Order By: Relevance
“…However, this does not appear to be utilized as an energy source (Harold 1966). Shaposhnikov and Fedorov (1960) reported that dark incubation of Chlorobium induced a slight degradation of polyphosphate, but the amount of polyphosphate mobilized was only about one-tenth of the total pool.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…However, this does not appear to be utilized as an energy source (Harold 1966). Shaposhnikov and Fedorov (1960) reported that dark incubation of Chlorobium induced a slight degradation of polyphosphate, but the amount of polyphosphate mobilized was only about one-tenth of the total pool.…”
Section: Discussionmentioning
confidence: 96%
“…The occurrence of polyphosphate bodies in cyanobacteria is well documented (Jensen 1968(Jensen , 1969Jensen and Sicko 1974). Jensen and Sicko (1974) are exposed to phosphate concentrations which are greater than required (Harold 1964). This storage activity is enhanced when cells are first starved of phosphate and then placed in a condition of high phosphate (Shapiro 1967).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations